(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Phrases describing the religious beliefs, the material content of worldviews, spiritual and cultural life of the people, that is, religious idioms in Arabic are found in sufficient numbers, the vast majority of them are connected with the influence of Islam, including Koranic verses, hadiths of Prophet Muhammad (SA a.), the statements of the Sahaba (companions).